Dialogues between Tactical Urbanism and Traffic Calming Measures in the (Re)Pensando Santana Program: Challenges and Potentialities - Novis, Raquel Lourenço Mendes; Marino, Cintia Elisa de Castro; Baiardi, Yara Cristina Labronici; Quaresma, Cristiano Capellani (National Journal of City Management, 2024)
New approaches to urban planning can promote inclusive projects that prioritize pedestrians. This involves readjusting existing public space, redesigning streets to guarantee comfort and safety for all users, with a focus on people. The present study analyzes the challenges and potential of the tactical urban planning intervention of the (Re)Pensando Santana program, implemented after interventions in the perimeter known as “Area 40”, both initiatives led by the City of São Paulo. This intervention sought to redesign the street to impact walkability and achieve greater safety for pedestrians. The research method used in this study is based on two theoretical perspectives, tactical urbanism and traffic moderation, in the data collection and analysis from public administration, in addition to obtaining data through field visits and interviews. While tactical urbanism interventions seek quick, low-cost solutions to improve public spaces, traffic calming measures aim to control the flow of vehicles, with the aim of improving the safety and quality of the urban environment. The results highlight that reducing speeds alone, despite being a significant advance in road safety, was not enough to improve public space. On the other hand, the articulation of the perspectives of temporary urbanism with traffic calming represented advances in security and in the transformation of the built environment, especially as a new urban planning process.